Impact of land-use change on soil erosion rates in Wonosalam Village, Wonosalam District, Jombang - Dewi Shasa Bella; Siswanto .; Maroeto . (Universitas Trunojoyo Madura, 2026)
Land use conversion in the hilly area of Wonosalam, Jombang Regency, has significantly altered vegetation cover, leading to increased soil erosion rates. This study aims to analyze soil erosion magnitude across various land use types and assess the impact of land conversion on erosion levels in Wonosalam Village in 2014, 2019, and 2024. A quantitative approach was applied using the Universal Soil Loss Equation (USLE) model combined with spatial analysis through Geographic Information System (GIS). Data sources include Landsat 8 imagery, land use maps, rainfall data, slope maps, and laboratory analysis of soil physical and chemical properties. Each erosion factor (R, K, LS, C, and P) was analyzed to estimate soil loss (A) in tons/ha/year. The results indicate that the conversion of forest areas into agricultural and residential lands significantly increases erosion rates, especially on slopes steeper than 25%. Conversely, forested areas with dense vegetation show the lowest erosion rates. These findings demonstrate a strong correlation between land use change and erosion acceleration. The study provides valuable insights for soil conservation planning and sustainable land management in the hilly regions of Wonosalam